Les STAPS peuvent-elles être une science propre? - Loic, J. (Movement & Sport Sciences - Science & Motricité, 2016)
The STAPS are crossed by at least two great types of epistemics these days, which won`t fail to have implications as to their organization and their future. The first type is the positivist one; it considers this university subject as applied science and the knowledge in sports as subsidiary creeds which are induced to disappear in a near future, that is as soon as researchers have found the science of reference corresponding to the gist of the STAPS. The second type is historical and reflects on the STAPS dismissing any form of ontology: this history is peculiar to networks which develop from conflicts, agreements or disagreements. Thus do we switch from the era of science to the era of relativism, and the STAPS topple over into adventure. We introduce a third type of epistemology, a realistic one, which shows that the STAPS are a science of their own: they are based on both a knowledge and practice of their own, which allow a better understanding of the wold of sports, of the physical education provided at school, of the academic character of the subject as well as of the physical value of man.